2017
DOI: 10.1016/j.jclinepi.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials and systematic reviews addressing similar interventions for the same condition do not consider similar outcomes to be important: a case study in HIV/AIDS

Abstract: BACKGROUND The usefulness of clinical trials and systematic reviews is compromised when they report different outcomes. We compared outcomes in reviews of HIV/AIDS and the trials included in the reviews. STUDY DESIGN AND SETTING We examined all Cochrane reviews of HIV/AIDS (as of June 2013) that included ≥ 1 trial, and the trials that the reviews included. We compared outcomes within subgroups defined by type of intervention: clinical management, biomedical prevention, behavioral prevention, and health servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Although we specified only a few outcome domains, RCTs assessed hundreds of different treatment effects within them [36]. Previous authors have argued that core outcome sets, which list the minimum outcomes to assess in research, could improve the comparability of trials [37,38] and improve the synthesis of trials for knowledge translation [39]. Although we agree, our results also show that efforts to develop core outcome sets might have little impact unless they define outcomes completely.…”
Section: Discussionsupporting
confidence: 55%
“…Although we specified only a few outcome domains, RCTs assessed hundreds of different treatment effects within them [36]. Previous authors have argued that core outcome sets, which list the minimum outcomes to assess in research, could improve the comparability of trials [37,38] and improve the synthesis of trials for knowledge translation [39]. Although we agree, our results also show that efforts to develop core outcome sets might have little impact unless they define outcomes completely.…”
Section: Discussionsupporting
confidence: 55%
“…23 These findings reflect discord among reviewers and trialists addressing the same disease, in addition to the increasing evidence of the inconsistency in outcome use among trials. Other systematic investigations of trials that addressed HIV infection and AIDS, 23 tinnitus, 24 cardiac arrest, 25 and critical care 26 have also demonstrated the absence of a single outcome that was reported across all trials. The proportion of outcomes reported in only 1 trial each has been reported to be high, ranging from 41% to 70%, for HIV infection and AIDS, 23 glaucoma, 13 cardiothoracic surgery, 27 and audiology.…”
Section: Discussionmentioning
confidence: 99%
“…4 We previously tested a framework for this approach for outcomes in trials and reviews that addressed HIV infection and AIDS. 23,38 Macefield and colleagues 39 also used a similar framework while identifying patient-reported core outcomes for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with guidance in the Cochrane Handbook for Systematic Reviews of Interventions [6], we believe that studies that address the population, interventions, and comparators of interest should be included and cataloged in systematic reviews even if they do not report outcomes of interest. Outcome choice in a review is crucial because: (1) outcomes serve as yardsticks for basing conclusions about treatments; and (2) which outcomes are chosen and how they are defined can impact how many meta-analyses can be done and how many studies can be included in them [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated, through case studies in the fields of eyes and vision [11] and HIV/AIDS [10], that reviewers and clinical trialists addressing the same research question often examine different outcomes. In addition, inconsistency in outcome reporting across eligible studies prevents incorporation of all eligible studies into meta-analyses.…”
Section: Introductionmentioning
confidence: 99%